Professional stress and burnout syndrome in teachers: are there differences among the Republic of Srpska regions? - Maric, Nada; Mandić-Rajčević, Stefan; Maksimović, Nataša; Bulat, Petar (Scripta Medica, 2021)
Introduction: Burnout syndrome occurs as a result of prolonged exposure to emotional and interpersonal stressors in the workplace and is characterised by three dimensions: emotional exhaustion, depersonalization and personal achievements. Research and prevention of this phenomenon are of public health importance due to numerous consequences it leaves on the health of the working population and work organisation, and among teachers, on children as direct users of their services. The research aims to examine the presence of the stress and burnout syndrome at work in teachers in the regions of the Republic of Srpska, as well as to determine the existence of differences between regions. Methods: The research was conducted as a cross-sectional study in the period August-September 2018, in the territory of the Republic of Srpska. The target population was represented by teachers of primary and secondary schools. The response rate in all regions was 75 % or above it. For this research, a special questionnaire was constructed, consisting of sociodemographic data, data on economic characteristics of the respondents, characteristics of the work environment, as well as data on satisfaction with equipment and resources at work, support from family and friends and presence of work-life conflict. In addition to the general questionnaire, the Maslach Burnout Inventory-Human Services Study (MBI-HSS) questionnaire for the assessment of the burnout syndrome at work, and Karasek’s questionnaire (Job Content Questionnaire) for the assessment of stress at work were used. Results: A statistically significant difference in the prevalence of occupational stress among teachers between RS regions was found. Also, a statistically significant difference was found between the regions of the Republic of Srpska related to the dimensions of burnout syndrome at work. A high level of emotional exhaustion was more often reported by teachers from the territory of the region of East Sarajevo and Prijedor (8.0 % and 7.7 %) comparing to teachers from other regions. Teachers from the territory of Prijedor more often showed moderate and high levels of depersonalization, as well as a low level of personal achievements comparing to teachers from other regions. Conclusion: This research shows the presence of burnout syndrome in teachers of all the Republic of Srpska regions at the beginning of the school year, as well as statistically significant differences between the regions. This indicates the need for additional research on risk factors by regions to form targeted and thus more effective prevention measures.